Chiral magnetic chemical bonds in molecular states of impurities in Weyl semimetals - Marques, Y. [UNESP]; Mizobata, W. N. [UNESP]; Oliveira, R. S. [UNESP]; de Souza, M. [UNESP]; Figueira, M. S.; Shelykh, I. A.; Seridonio, A. C. [UNESP] (Springer Nature, 2019)
We demonstrate that chirality of the electron scattering in Weyl semimetals leads to the formation of magnetic chemical bonds for molecular states of a pair of impurities. The effect is associated with the presence of time-reversal symmetry breaking terms in the Hamiltonian which drive a crossover from s- to p-wave scattering. The profiles of the corresponding molecular orbitals and their spin polarizations are defined by the relative orientation of the lines connecting two Weyl nodes and two impurities. The magnetic character of the molecular orbitals and their tunability open the way for using doped Weyl semimetals for spintronics and realization of qubits.